Association between pan-immune-inflammation value and coronary heart disease in elderly population: a cross-sectional study - Ruicong Ma; Jinyi Ren; Xianmei Chen; Xia Li; Ying Zhao; Yanchun Ding (Frontiers in Cardiovascular Medicine)
BackgroundSystemic inflammation, immune and nutrition status are closely linked to the occurrence and development of coronary heart disease (CHD). Pan-immune-inflammation value (PIV) is a new method for evaluating systemic inflammation and immune status. Our objective is to explore the connection between PIV and CHD especially in elderly people, as well as the diagnostic value of PIV combined with controlling nutritional status (COUNT) score for CHD.MethodsParticipants eligible for the study were sourced from NHANES data from 1999 to 2018. Logistic regression models were employed to evaluate the link between PIV and CHD. Additionally, restricted cubic spline was utilized to explore the correlations. Subgroup analysis was adopted in order to ensure the credibility of the results. The receiver operator characteristic (ROC) curve was used to explore the predictive value of PIV combined with COUNT score for CHD.Results41,713 individuals qualified for analysis. The individuals with CHD had higher levels of PIV. In the logistic regression model, PIV was positively related to CHD [Q4 vs. Q1, OR = 1.23 (1.03–1.48, P < 0.001)]. Restricted cubic spline indicated a positive non-linear relationship (P for overall <0.001, P for non-linear = 0.009). However, restricted cubic spline shows that this positive correlation is only significant in the elderly population aged 60 and above. Subgroup analysis shows that the relationship between PIV and CHD is more significant in the elderly population (P < 0.001). The ROC curve shows that PIV has better diagnostic value for CHD than other common inflammatory indicators. Furthermore, the combination of PIV and COUNT score is superior to PIV or COUNT score.ConclusionsA positive link between PIV and CHD, especially in the elderly. The combination of PIV and COUNT score has better diagnostic value for CHD.